The Body and the Body Politic: Assisted Suicide under the Canadian Charter of Rights and Freedoms Case Comments - Weinrib, Lorraine Eisenstat (McGill Law Journal, 1993)
Disclaimer: This summary was generated by AI based on the content of the source document.